Does data disclosure increase citations? Empirical evidence from a natural experiment in leading economics journals - Mark J. McCabe; Frank Müller-Langer (European Commission, Joint Research Centre (JRC), 2019)
Does data disclosure have an impact on citations? Four leading economics journals introduced a data disclosure policy between 2004 and 2006. We use panel data consisting of 17,135 article citing-year observations from 1996 to 2015 for articles published in these journals. Empirical articles that did not disclose data (46% of the sample) serve as a control group. Evidence for a positive open data citation effect is weak (6% and not statistically significant). On the other hand, the citation impacts of publication are substantial and precisely estimated. Pure theory, hybrid and purely empirical articles enjoy citations benefits of 22%, 32% and 44%, respectively. Our pre- and post-publication citation data allow us to identify the citation effects of data disclosure and publication, while controlling for intrinsic article quality.
Keywords: L17; O33; C80; L59; 330; Data disclosure; diffusion of knowledge; natural experiment; panel data